DMYTRО DONTSOV’S TEXTS IN THE ASPECT OF CORPUS LINGUISTICS AND LEXICOGRAPHY - Oksana R. Mykytyuk; Liliia V. Kharchuk (Alfred Nobel University Journal of Philology)
Increasingly, computer technologies in linguistics offer their advanced tools to process, store and select language data, which has triggered the fast development of the actual branch of linguistic studies – corpus linguistics. Through the use of large-scale empirical data and advanced computer technologies to reach objective insights into language function, linguistic corpora have quickly become invaluable resources. Data obtained through corpus analysis facilitate the drawing of qualitatively new conclusions about language and highlight research directions that previously received little attention. Despite substantial linguistic work on Dmytro Dontsov’s writings, there still exist a number of questions not studied so far. Among these are compiling a linguistic language corpus as well as a concordance of this prominent thinker, public figure, publicist utilizing modern methods to calculate and fix lexemes in order to identify their attributive collocation. Any available means of programming, facilitating processing language material of a big mass, have been realized to be an undoubtedly productive way to properly perform conceptual analysis and to serve as an additional tool for studying. The purpose of the study is to determine the peculiarities of the unique features of Dmytro Dontsov’s maxims in the aspect of corpus linguistics and lexicography on the basis of the corpus space that forms the linguistic vision of the world and is a source of creating lexicographical pieces of work (concordances, a writing language, a writer language, etc.). We emphasize that the creation of Dmytro Dontsov’s writing concordance has become the subject of corpus linguistics study for the first time. The subject of our study is the writings of Dmytro Dontsov, their lexicographical parametrization which provides all possible words with their description (phonetic, word-creating, grammatical), along with quantitative indices, i.e. it is the result of learning many linguistic disciplines, unified by the dictionary. The methodology of study is the combination of general theoretical methods (analysis, generalization, explanation) with the applied methods of linguistics. Analysis of the studied conception is grounded in “The Spirit of Our Antiquity” text corpus compiled by using the Sketch Engine program. On the basis of the analysis, it is found out that an electronic corpus provides the opportunity to accelerate language study and increase its effectiveness, probability and checkability significantly. The article reveals heuristic potential, practical effectiveness of the corpus and application of concordant technologies in conceptual studies. It was discovered that, the construction of the full concordance of the writings of Dmytro Dontsov will enable showing the picture of the world on the basis of learning the author’s lexical wealth and reproducing his understanding of the political situation. The created concordance is a stage of forming lexicographical works about Dontsov, which provides understanding of stages, methods, principles and peculiarities of compiling Dmytro Dontsov’s writing language dictionary. The multifaceted study of D. Dontsov’s writings is believed to be of importance. The concordance serves as a new material, important for politicians, journalists, teachers, students, for it is an entrance in a system of new words, filling with new ideas, and possibility to perceive the world through the nation-state aspirations of a great thinker. Realization of his project will help to create a political-intellectual product of great importance to offer bright prospects for future linguistic study, whose tasks are supposed to use linguistic material.